Use of information and communication technology to access tourist information and services: The results of research conducted among Polish tourists in Małopolska Voivodeship - Pawłowska-Legwand, Aneta (Turyzm/Tourism, 2019)
Information and communication technology (ICT) is widely used to access tourist information and services, and as a result using digital tools and sources influences tourist behaviour. The main goal of this paper, based on research, is to describe the behaviours and opinions of tourists who used ICT before travelling. The results include the evaluation of the usefulness of digital tools from a tourist’s point of view, and indicates that tourists are interested in using ICT. Respondents aged over 35, who are living in cities and have had at least secondary education or a university degree, are more active users of digital tools. Websites, mobile applications and other ICT uses have been treated by respondents primarily as a source of tourist information in its widest sense, and a tool which facilitates the process of planning travel routes and purchasing travel-related services. Social media, which facilitate sharing travel-related content, also have a major significance.